1987
DOI: 10.1123/jsp.9.1.15
|View full text |Cite
|
Sign up to set email alerts
|

The Relation off Knowledge Development to Children's Basketball Performance

Abstract: This study examined the relationship of sport-specific knowledge to the development of children's skills in basketball. Two experiments were conducted. The first compared child expert and novice basketball players in two age leagues, 8-10 years and 11-12 years, on the individual components of basketball performance (control of the basketball, cognitive decisions, and motor execution) and on measures of basketball knowledge, dribbling skill, and shooting skill. Child expert players of both age groups possessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
0
101

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(274 citation statements)
references
References 19 publications
9
164
0
101
Order By: Relevance
“…Studies show that athletes in U-15 teams display differences in declarative tactical knowledge, which is in accordance with the findings of the present study. these differences were found among basketball players from U-10 and U-12 youth teams [10], among soccer players when comparing players aged 8-12 years [28], among soccer players from U-14 and U-16 youth teams [19], and among U-14 soccer teams as compared with those from U-15 and U-17 youth teams [29]. As for athletes from U-15 youth teams on, studies show that there is no difference between the U-15 and U-17 players' declarative tactical knowledge [29] or among U-15, U-17, and U-20 squads [20].…”
Section: Ethical Approvalmentioning
confidence: 80%
See 1 more Smart Citation
“…Studies show that athletes in U-15 teams display differences in declarative tactical knowledge, which is in accordance with the findings of the present study. these differences were found among basketball players from U-10 and U-12 youth teams [10], among soccer players when comparing players aged 8-12 years [28], among soccer players from U-14 and U-16 youth teams [19], and among U-14 soccer teams as compared with those from U-15 and U-17 youth teams [29]. As for athletes from U-15 youth teams on, studies show that there is no difference between the U-15 and U-17 players' declarative tactical knowledge [29] or among U-15, U-17, and U-20 squads [20].…”
Section: Ethical Approvalmentioning
confidence: 80%
“…In sport, procedural tactical knowledge is related to perceptive-cognitive-motor skills and refers to an appropriate action in a game, in the context of know-how. Declarative tactical knowledge is related to tasks, mnemonic structures of the tasks, considering the knowledge about the rules and objectives of a game, and refers to knowing what to do [10].…”
Section: Introductionmentioning
confidence: 99%
“…Deemphasizing competition and recognizing that a coach's task with young children is to maintain interest, motivation, and participation seem to be necessary preconditions to avoid creating dropouts. French and Thomas (1987) point out that both cognitive and motor skills are important for children's sport development. Optimal coaching should therefore not exclusively concentrate on motor skills, but also devote time to teaching sportspecific procedural knowledge and cognitive skills such as knowledge of the rules of the game, optimal player positions, and game strategies (Bunker & Thorpe, 1983).…”
Section: Warning Practitionersmentioning
confidence: 99%
“…Studies using sorting methods have shown that experts classify problems according to underlying functional principles, whereas novices operate more strongly with superficial features (Allard & Burnett, 1985;Russell & Salmela, 1992). Furthermore, questionnaire methods and interviews have revealed the structure and organization of movement knowledge in, for example, tennis (McPherson & Thomas, 1989, McPherson & Kernodle, 2003, Volleyball (McPherson & Vickers, in the part I of this special issue) and basketball (French & Thomas, 1987).…”
Section: Structure Formation In Long-term Memorymentioning
confidence: 99%